Penanganan Pemukiman Kumuh Perspektif Islam: (Studi kasus Pemukiman di Kelurahan Maccini Sombala, Kota Makassar) - Suriyani (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2024)
The slum settlement in Maccini Sombala, Makassar City, Indonesia, poses serious challenges to residents' well-being. Issues such as inadequate housing, poor sanitation, and limited access to clean water create health risks and social inequality. A social empowerment approach is considered essential, motivating the community as agents of change to improve living conditions. However, implementation faces resource constraints and the complexity of land ownership issues. This research combines qualitative and quantitative methods to analyze the impact of social empowerment, measure residents' quality of life, and evaluate the effectiveness of empowerment programs. The article aims to provide a comprehensive overview to enhance social empowerment strategies in addressing slum settlements in Maccini Sombala. Results indicate that community participation, capacity building, infrastructure, and local economic empowerment are crucial in overcoming slum challenges, fostering sustainable development, and alleviating poverty.